2019
DOI: 10.1088/1674-1056/ab3445
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of urea under high pressure and high temperature*

Abstract: The properties of urea under high pressure and high temperature (HPHT) are studied using a China-type large volume cubic high-presentation apparatus (CHPA) (SPD-6 × 600). The samples are characterized by scanning electron microscopy (SEM), x-ray diffraction (XRD), and Raman spectroscopy. By directly observing the macroscopic morphology of urea with SEM, it is confirmed that the melting point of urea rises with the increase of pressure. The XRD patterns of urea residues derived under different pressures show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As can be seen, the intensity of the Pd peak increases in the following order: Pd/CNF-U < Pd/CNF-Cl < Pd/CNF-N < Pd/CNF, as did the mean NP sizes (Table 1). Pd/CNF-U shows two other peaks at around 33 • and 36 • related to the urea [25]. Probably, the interaction between urea and CNF is forming N-doped CNF.…”
Section: Characterization Resultsmentioning
confidence: 97%
“…As can be seen, the intensity of the Pd peak increases in the following order: Pd/CNF-U < Pd/CNF-Cl < Pd/CNF-N < Pd/CNF, as did the mean NP sizes (Table 1). Pd/CNF-U shows two other peaks at around 33 • and 36 • related to the urea [25]. Probably, the interaction between urea and CNF is forming N-doped CNF.…”
Section: Characterization Resultsmentioning
confidence: 97%
“…The main XRD reflection of urea (100) has a bifurcated shape (maximums at 21.87 and 22.05°). Furthermore, this reflection of the crystalline urea incorporated into the silicate–xerogel structure shifted in the lower 2θ-angles range in comparison with pure crystalline urea [ 17 , 18 ] or crystalline urea mechanically mixed with the urea-free xerogel ( Figure 3 b, maximum at 22.4°). The XRD patterns of the obtained xerogels indicate that a quantity of planes and d-values of urea, incorporated into the silicate matrix, changed in comparison with pure crystalline urea, similar to [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Carbonization is a necessary process in the transformation of hydrocarbon to diamond, which involves many complex reactions such as polymerization, poly-condensation, cracking reactions, molecular rearrangement, and hydrogen transfer. [41][42][43][44][45] Carbon intermediates with different crystallinities are obtained in samples NX (X = 5-8) by using different carbonization time at 11.5 GPa and 700 • C. Their crystallinity increases with increasing carbonization time. It has been suggested that diamond nucleation is more likely to occur with carbon nanoparticles containing amorphous carbon as a precursor, [46][47][48][49] and that the quantity of nucleation and granularity of synthesized nanodiamonds decrease with increasing crystallinity of the graphite precursor.…”
Section: Resultsmentioning
confidence: 99%